An Authentication Scheme For Free-Space Laser Communication Using "Fingerprint-Matching" - Chowdhury, Subhajit Dutta; Chakraborty, Rijuparna (2020 4th International Conference on Electronics, Materials Engineering & Nano-Technology (IEMENTech), 2020)
An authentication scheme for free-space communication with singular laser beam has been discussed. A known order of singularity was imposed on the beam, which generates its characteristic fingerprint structure. At the receiver end, in order to check that fingerprint pattern, a part of the received beam was first interfered with a locally generated plane wave and then Fourier transformed. This frequency distribution pattern, captured by a CCD camera, gives the final fingerprint pattern of the known order vortex beam. An application software compares this pattern with the previously stored ones and generates a 'high' signal upon successful match. This 'high' signal eventually set the final AND gate open for passing the digitized message through it.